تأثير مواعيد الزراعة والتسميد الأزوتي في بعض الصفات النوعية لثمار الكمون(Cuminum cyminum L.) - عبد العزيز محمد; بوعيسى عبد العزيز; سليمان سوازان (Latakia University Journal -Biological Sciences Series, 2018)
This study was carried out in Jeb Ramli town, Alghab region to investigate the effect of three planting dates (1 Feb. ,15 Feb. ,1 March) and four level of nitrogen fertilization ( 0, 40 ,60 , 80) Kg/h with interactive effect between them on some yield quality propareties in Cumin . the factors were arranged in a spilt plot in a randomized on plete block design with three replicates . the planting dates were assigned to the main plots and the levels of nitrogen fertilization were factorially assigned to the sub plots . the study showed the following results : 1- planting dates (15 Feb. and 1 March ) had significantly better effect tham 1 Feb. planting date on Nitrogen content (3.03 , 3.09 )% and 2.91% respectively and on carbohydrate percentage (1.99,2.12)% and 1.88% respectively 2- planting date (1 Feb.) significantly increased the percentage of essential oil 23.08% and percentage of volatile oil 3.63% as compared to the planting dates (15 Feb. and 1March) (22.33 , 22.77)% and (3.54 , 3.41 )% respectively 3-Nitrogen fertilization (40 and 80 ) Kg/h had significantly better effect on most traits under study except carbohydrate percentage and fiber highest value of percentage of volatile oil 3.83 % and protein content 20.15 % occurred at 80 kg/h nitrogen fertilization 4-the interaction of factors had significant effect on most traits under study , the highest value of percentage of essential oil 23.6% and percentage of volatile oil 3.93% and protein content 20.49% were occurred at( 1 Feb.* 40 kg/h) , ( 1 Feb. * 80 kg/h ) and ( 1 March* 80 kg/h ) respectively . نفذ البحث خلال الموسم الزراعي 2015 م في قرية جب رملة ، منطقة الغاب لدراسة تأثير ثلاثة مواعيد للزراعة ( 1 شباط ،15 شباط ،1 آذار ) ، وأربعة معدلات للتسميد الآزوتي (0 ، 40 ،60 ، 80 ) كغ/ه ، والتفاعل بينهما في بعض الصفات النوعية لثمار الكمون ، استخدم تصميم القطاعات العشوائية الكاملة بنظام القطع المنشقة لمرة واحدة . شغلت مواعيد الزراعة القطع الرئيسية ، ومعدلات التسميد الآزوتي القطع الثانوية في ثلاث مكررات بينت الدراسة النتائج الآتية : 1- تفوق موعدي الزراعة الثاني والثالث ( 15 شباط و 1آذار) في نسبة الآزوت فكانت (3.03 و 3.09) (%) والكربوهيدرات (1.99 و2.12) (%) على الموعد الأول1 شباط فكانت القيم 2.91(%) و1.88(%) على التوالي . 2- اعطى موعد الزراعة الأول 1 شباط زيادة معنوية في نسبة الزيت الثابت 23.08(%) ونسبة الزيت العطري 3.63(%) مقارنة بالموعدين الثاني والثالث (22.93 ، 22.77) (%) و (3.54 ، 3.41 ) (%) على التوالي . 3- تفوقت جميع معدلات التسميد الآزوتي 40 - 80 كغ/ه معنوياً على الشاهد في جميع الصفات المذكورة باستثناء نسبة الكربوهيدرات والألياف . واعطى المعدل 80 كغ/ه أعلى نسبة زيت عطري 3.38(%) وأعلى نسبة بروتين 20.15 (%) . 4- اعطى التفاعل بين مواعيد الزراعة ومعدلات التسميد الآزوتي تأثيراً معنوياً في جميع الصفات المدروسة فوجدت أعلى نسب للزيت الثابت 23.60(%) ، وللزيت العطري 3.93(%) ، والبروتين 20.49(%) عند التفاعل بين الموعد( 1 شباط × المعدل 40 كغN/ه ) والموعد( 1 شباط × المعدل 80 كغN/ه) ، والموعد ( 1 آذار × المعدل 80 كغN/ ه) على التوالي .